Avoiding Arch Manipulation with Catheterization of Left Subclavian Artery for Endovascular Repair of Distal Descending Aorta: Acibadem Technique. Issue 2 (March 2020) - Senay, Sahin; Akansel, Serdar; Güllü, Ahmet Ümit; Alhan, Cem
Although thoracic endovascular aortic repair (TEVAR) is associated with reduced mortality and shorter hospital stay compared to open surgery, the decrease in stroke risk did not reach the desired rates. Aortic arch manipulation is one of the main concerns leading to stroke during TEVAR. Here, we describe a new technique called "Acibadem Technique" to avoid arch and ascending aorta manipulation with catheterization of left subclavian artery for endovascular distal descending aortic repair.